A diffusion-driven fabrication technique for anisotropic tubular hydrogels. Issue 37 (6th September 2018) - Mredha, Md. Tariful Islam; Tran, Van Tron; Jeong, Sin-Gu; Seon, Jong-Keun; Jeon, Insu
Abstract : A bio-inspired, simple, and versatile diffusion-driven method to fabricate complex tubular hydrogels is reported. Abstract : A bio-inspired, simple, and versatile diffusion-driven method to fabricate complex tubular hydrogels is reported. The controlled diffusion of small ions from a pre-designed core hydrogel through a biopolymer reservoir solution causes the self-gelation of biopolymers with an anisotropic ordered structure on the surface of the core hydrogel. By controlling the concentration, diffusion time, and flow direction of the ions, as well as the size and shape of the core, various types of complex tubular-shaped hydrogels with well-defined 3D architectures were fabricated. The mechanical properties of the designed alginate-based tubular hydrogels were highly tunable and comparable to those of native blood vessels. The method was applied to form a living-cell encapsulated tubular hydrogel, which further strengthens its potential for biomedical applications. The method is suitable for biopolymer-based reaction–diffusion systems and available for further research on the fabrication of functional biomaterials with various biopolymers.